Mengartikulasikan Tabel Input-Output dan Kerangka Analisisnya - Budi Cahyono; Bagus Sumargo (The Winners, 2005)
Input -Output (I-O) table can be used to analyse economic projection and present some service and good transactions in production activities, final demand, and bruto added value (BAV). I-O table can help to analyse government policy, such as impact analysis to output, bruto added value, and worker needed.